Association between non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) with depressive symptoms: recent findings from NHANES 2005–2018 - Yan, Chunyu; Wang, He; Liu, Changxing; Fu, Jiamei; Zhou, Yabin (Frontiers in Psychiatry, 2024)
The ratio of non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol (NHHR) index is a relatively new composite lipid index,the relationship between NHHR and depression is unclear from the current study.The primary aim of our study was to examine the association between the prevalence of depression and NHHR in a US population.provided the data for our investigation from 2005 to 2018. and primarily included participants who contained complete data on NHHR and depression in U.S. adults (age ≥20 years). Associations between NHHR and depression were assessed using multifactorial logistic regression analysis,subgroup analysis, and smoothed curve fitting.Results:In our study, 29,561 subjects in total showed a mean NHHR index of 3.12± 1.58,A noteworthy positive correlation was observed between NHHR and depression in multifactorial logistic regression analysis.Subgroup analyses and tests of interaction showed that gender, age, ethnicity, PIR, smoking, alcohol consumption, coronary heart disease, diabetes mellitus, hypertension, and stroke did not influence the NHHR and the association between depression (P for interaction > 0.05), whereas two stratification factors, BMI and sleep disturbance, may be potential factors in the association between NHHR and depression (P for interaction < 0.05).According to our present study, if the level of NHHR rises in American adults, their likelihood of developing depression also increases.